The Effects of Blade Angle on Blade Stresses During Cutting of Different Kinds of Paper Materials - (:unkn) unknown (ASSOC MECHANICAL ENGINEERS TECHNICIANS SLOVENIA, 2009)
In the printing sector knives (blades) are used during pre-printing, printing and post-printing. Therefore, paper type, blade angles, the sharpness of blades and applied pressure are all important factors in terms of cutting quality. In this study, during the cutting of different kinds of paper material, the effects of blade angle on blade stresses has been investigated Using paper pulp I, paper pulp II, coated paper and Bristol paper various analyses have been made. In the analyses, according to changes to blade angles of 20, 22, 24, 26, 28 and 30 degrees changes have been observed in maximum principal stress, S(1), minimum principal stress, S(3) and von Mises stresses, S(EQV), In conclusion; since Von Mises stresses and especially max. compressive stresses (min. principal stress, S(3)) occurred at the lowest level for paper pulp I, paper pulp II, coated paper and Bristol papers, it has been decided that fir increased durability of the knife the critical blade angle in terms of abrasion/breakage of the blade should be 28 degrees rather than the more widely used angle of 24 degrees. A blade angle below 22 degrees is not advised (C) 2009 Journal of Mechanical Engineering. All rights reserved.
Keywords: paper; blade; stress; ANSYS